Brain Drain: A Cross-Sectional Study Evaluating Migration Intentions of Neurosurgery Trainees in Pakistan - Shakir, Muhammad; Altaf, Ahmed; Irshad, Hammad Atif; Khan, Muhammad Ali Akbar; Enam, Syed Ather (Asian Journal of Neurosurgery, 2024)
Background Pakistan has a significant proportion of medical graduates who intend to leave the country for better opportunities abroad, leading to a brain drain. However, the push and pull factors within neurosurgery remain unexplored, emphasizing the need for evaluation to enact policy changes.Materials and Methods We conducted a nationwide survey across 22 College of Physicians and Surgeons of Pakistan accredited neurosurgery training centers in all provinces of Pakistan. SPSS version 26 and STATA 15 were used for data analysis.Results We collected responses from 120 neurosurgery trainees across Pakistan. Trainees were categorized into two groups: those intending to leave (64%) and those intending to stay (36%) in Pakistan. A significant association was observed between the availability of fellowship training in the residents' hospital and the decision to leave or remain in Pakistan (p = 0.034). About 67.5% of our respondents did not have any publication, and among the intention to leave group, a greater percentage had academic involvement, when compared with the stay group. A significant association (p = 0.012) was also observed between the decision to leave or remain in Pakistan and the number of publications in nonindexed journals.Conclusion There remains a need for improvement in the standard of training provided by neurosurgery programs across the country. Our study found that disparities in research and academic exposure, as well as the lack of fellowship opportunities, may serve as stimuli for residents to leave Pakistan.
Keywords: migration intention; brain drain; trainees; fellowship; neurosurgery